Kemitraan CV Bumi Kopi dengan Petani di Desa Sukamekar - Muhamad Ilham; Ema Hilma Meilani; Endang Tri Astutiningsih (Jurnal Surya, 2022)
The agricultural sector in Indonesia an important role in the economy, especially the coffee plantation sector. Coffee is one of the quality plantation products and has a high economic value. However, coffee farmers need partners to enter the market at high prices, and the problem faced in the implementation of farm partnership cooperation is the imbalance between the implementation of the cooperation model and the level of economic benefits obtained. The purpose of this study is to outline the partnership between coffee farmers and CV Bumi Kopi, a marketing partner that produces coffee. The research method used is a quantitative research method with a qualitative description. The data collection method is the purposive sampling method.The results of this study show that the pattern of partnership carried out between farmers and CV bumi kopi is the partnership pattern of Agribusiness Operational Cooperation (KOA), which is a partnership pattern which is a business relationship run by a partner group with partner companies.